Standardized functional capacity outcome measures in post-operative cardiac surgery: A survey of current clinical practice and development of a clinical practice guideline (CPG) - Mac Donald, Tanya (University of Ottawa (Canada), 2009)
The objectives of the thesis were to determine the prevalence of functional capacity outcome measure use among physiotherapists working with post-operative cardiac surgery clients and to develop evidence-based recommendations regarding their use in clinical practice. The thesis consisted of a systematic review of the literature; a survey of outcome measure use in clinical practice; and the development of a clinical practice guideline. Thirty-one functional capacity outcome measures were included in the review. Only 2.6% of survey respondents reported almost always using outcome measures in their clinical practice. The Six Minute Walk Test, the modified Borg Rating Scale of Perceived Exertion and vital signs were recommended for routine use in clinical practice. A variety of outcome measures are available for use in clinical practice however their use in clinical practice continues to be less than optimal. There is a need for continued training in outcome measure use in clinical practice.
Keywords: Health Sciences, Medicine and Surgery.; Health Sciences, Surgery.